The Influence of Embeddedness on Entrepreneurship, Innovation and Strategy: A Gender Perspective in the Agri-Food Sector - Santos, Gina (2021)
This study aims to identify the antecedents of entrepreneurial activity in the agri-food sector of the Portuguese region of Trás-os-Montes and Alto Douro (TMAD), taking into account a gender perspective. Thus, we intend to assess whether the environment influences embeddedness, and whether embeddedness, individual entrepreneurial orientation, innovative behaviour and gender impact or influence the perceptions of feasibility and desirability as antecedents of entrepreneurial activity of entrepreneurs in the agri-food sector of the TMAD region. The measurement instrument was applied to 249 firms in the agri-food sector, created in the last 5 years. A model was conceptualised where the relationships between the constructs relating to embeddedness, IEO and EI were presented, and three control variables were subsequently added: the innovative behaviour, the environment and gender. Univariate and multivariate statistical techniques, such as structural equation modelling, were used to assess the proposed conceptual model. Thus, considering the complexity of the model under study, we performed an analysis which considered personal factors or characteristics, such as innovative behaviour, gender and IEO, as these are characteristics of the individual and may be influenced or shaped by external factors such as the context, i.e., the environment and embeddedness.